Study of different polymer coating on sugar beet seed germination characteristicsand plant establishment - مهناز چنگیزیان; قاسم توحیدلو; پیمان فروزش (علوم و فناوری بذر ایران)
The present study was designed to evaluate the effect of seed coating on Monogerm beet seed viability and development by using four different polymers in 2013in Research Institute for Improvement of Sugar Beet Seed. The experiment was conducted on the basis ofa completely randomized design with four replications. Monopolymer (MP), Copolymer (CP), Homopolymer hard (HPS) and soft Homopolymer (HPS), each at a concentration of, 1, 5, and 10 % with control (uncoated) were compared. The recorded traits included germination immediately after coverage, after one month of coverage, growth power after three months of coverage, fresh weight, dry weight, number of buds, shoot length, root length, and growth power of seed in the field. The results showed that there were significant differences among treatments in terms of all traits. According to the results, both soft and hard Homopolymer hay were relatively superior in terms of most recorded traits. However, with respect to percent germination percentage in the field which is of great importance, Monopolymer 10% with Homopolymer hard and soft at low concentrations (to 5%) exhibited a good performance.